Seasonal variation of organic matter concentration and characteristics in the Maji ya Chai River (Tanzania): Impact on treatability by ultrafiltration - Aschermann, G.; Jeihanipour, A.; Shen, J.; Mkongo, G.; Dramas, L.; Croué, Jean-Philippe; Schäfer, A. (IWA Publishing, 2016)
Many waters in Tanzania exhibit high concentrations of organic matter and dissolved contaminants such as fluoride. Due to bacteria and virus removal, ultrafiltration (UF) is an attractive option for drinking water treatment, and when coupled with adsorbents, may compete with other established processes like nanofiltration (NF) for lower contaminant concentrations. The results presented here examine the characteristics and treatability of tropical natural organic matter (NOM) by UF as a function of seasonal variation.The Tanzanian river Maji ya Chai was sampled monthly during one year. The composition of NOM in Maji ya Chai River is influenced strongly by precipitation. Total organic carbon (TOC), specific ultraviolet absorbance (SUVA) and concentration of allochthonous organics substances (such as humic substances (HS)) are elevated in periods following high precipitation, while TOC is lower and contains more biopolymers in the dry seasons.UF experiments with two regenerated cellulose membranes of different molecular weight cut-off (MWCO, 5 and 10 kDa) were conducted. UF is able to remove 50-95% of TOC with a seasonal variability of 10-20%. Due to the remaining NOM in the water that would contribute to disinfection by-product formation and bacterial regrowth, the physically disinfected water is more applicable for point of use systems than distribution or storage.